2021
DOI: 10.1016/j.jdeveco.2021.102667
|View full text |Cite
|
Sign up to set email alerts
|

The long road to health: Healthcare utilization impacts of a road pavement policy in rural India

Abstract: Despite demand-stimulation efforts, coverage rates of many essential health services remain low in developing countries, suggesting that there may be binding supply constraints, such as poor access. This paper utilizes quasi-random variations in roadpavement intensity to study the impact of improved access on adoption of reproductive health services. I find that road construction led to higher rates of institutional antenatal-care and deliveries, which translated into better medical care and vaccination covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 91 publications
2
15
0
Order By: Relevance
“…Cable TVs can also affect fertility through another channel: the broadcasted programs can increase households' exposure to family planning methods, which could subsequently increase contraceptive use (La Ferrara, Chong, and Duryea 2012;Tasciotti, Sulehria, and Wagner 2022). On the other hand, infrastructure spending can help alleviate poverty (Khandker, Bakht, and Koolwal 2009;Gibson and Rozelle 2003;Lenz et al 2017;Parikh et al 2015), improve household welfare (Khandker, Barnes, and Samad, 2013;Saing 2018;Medeiros, Saulo Marques Ribeiro, and Vasconcelos Maia do Amaral 2021), and facilitate access to institutional health care (Aggarwal 2021) and schooling (Khandker and Koolwal 2011). Moreover, improvements in health infrastructure, such as via malaria eradication programs, can also increase fertility (Lucas 2013;Apouey, Picone, and Wilde 2018) by boosting fecundity among the beneficiary cohorts (Bhattacharjee and Dasgupta 2022).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Cable TVs can also affect fertility through another channel: the broadcasted programs can increase households' exposure to family planning methods, which could subsequently increase contraceptive use (La Ferrara, Chong, and Duryea 2012;Tasciotti, Sulehria, and Wagner 2022). On the other hand, infrastructure spending can help alleviate poverty (Khandker, Bakht, and Koolwal 2009;Gibson and Rozelle 2003;Lenz et al 2017;Parikh et al 2015), improve household welfare (Khandker, Barnes, and Samad, 2013;Saing 2018;Medeiros, Saulo Marques Ribeiro, and Vasconcelos Maia do Amaral 2021), and facilitate access to institutional health care (Aggarwal 2021) and schooling (Khandker and Koolwal 2011). Moreover, improvements in health infrastructure, such as via malaria eradication programs, can also increase fertility (Lucas 2013;Apouey, Picone, and Wilde 2018) by boosting fecundity among the beneficiary cohorts (Bhattacharjee and Dasgupta 2022).…”
Section: Related Literaturementioning
confidence: 99%
“…Improvements in road connectivity can also facilitate the expansion of public and private transport services (Asher and Novosad 2020), mitigate mobility barriers, and potentially improve households' access to formal health care. In doing so, rural roads can raise the rates of both institutional deliveries and immunization among children (Aggarwal 2021), which could reduce infant mortality. A decline in infant mortality could, in turn, further reduce fertility, 1 because it allows households to more easily achieve their desired family size (Kalemli-Ozcan 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One example of an effective transport initiative is the provision of subsidised travel through the distribution of transport vouchers, enabling women to access free transport to healthcare facilities for antenatal, delivery and postnatal care [77]. Improvements to existing public transport as well as road development would also enable more reliable and more widely available transport, allowing more women to access healthcare facilities [78]. However, our analyses also showed that women with reduced control over healthcare decisions had reduced utilisation, suggesting that the people who have control over the decisions, usually a partner or mother-in-law, underestimate the importance of maternal healthcare.…”
Section: Plos Onementioning
confidence: 99%
“…Related work in Minten, Koru, and Stifel (2013) also focuses on remoteness and profitability and documents significant farmer-to-retailer transaction costs to reach price-controlled input cooperatives in a rugged region in northern Ethiopia. 3 Our paper is related to a rapidly growing literature about the effect of roads or other infrastructure improvements on development outcomes and on the spatial distribution of economic activity, 4 which includes a whole host of outcomes other than just prices, including consumption diversity, farm investments, human capital investment, migration, and occupation choice (Aggarwal, 2018a; b; Adukia et al, 2016; Asher and Novosad 2016; Brooks and Donovan, 2017; Morten and Oliveira 2016). In our paper, we focus narrowly on the specific effect of transportation costs on market access (i.e.…”
Section: Introductionmentioning
confidence: 99%